Neue Perspektiven im Vormundschafts- und Pflegschaftsrecht 9. Göttinger Workshop zum Familienrecht 2010 - Coester-Waltjen, Dagmar; Lipp, Volker; Schumann, Eva; Veit, Barbara (Universitätsverlag Göttingen, 2011)
This volume contains reports of the 9th Workshop for Family Law held in Göttingen, Dec. 10th, 2010.